Combined flexor carpi ulnaris and flexor carpi radialis transfer for restoring elbow function after brachial plexus injury. Issue 7 (17th July 2019) - Atthakomol, Pichitchai; Ozkan, Sezai; Chen, Neal; Lee, Sang-Gil
Abstract : The result of combined agonist and antagonist muscle innervation in traumatic brachial plexus injury through the intraplexal fascicle nerve transfers with the same donor function has not yet been reported. We describe a patient with a C5–C7 traumatic brachial plexus injury who had a combined transfer of the flexor carpi radialis (FCR) fascicle to the musculocutaneous nerve and the flexor carpi ulnaris (FCU) fascicle to the radial nerve of the triceps. The patient returned for his follow-up visit 2 years after his surgery. The muscle strengths of his triceps and biceps were Medical Research Council grade 2 and 0, respectively. Compared with his uninjured side, his grip strength was 9.8%, and his pinch strength was 14.2%. Our case report provides insights on result of combined agonist and antagonist muscle innervation through combining the motor fascicle of the FCR and FCU to restore the elbow flexor and extensor. The result may not be promising.